DFT and dynamic simulations of OleuoPectin structures as a potential anticoagulant agent - Mona T. M. Ghanem; Heba D. Hassanein; Ahmed F. El-Sayed; Medhat A. Ibrahim; Ahmed M. Bayoumy (Scientific Reports)
Abstract Oleuropein, a biologically active compound with variable pharmacological properties, is poorly absorbed in the gut, causing gastrointestinal upset in sensitive individuals. Model molecules of Oleuropein, pectin, and some proposed interactions were built up and geometrically optimized via both semiempirical and DFT high theoretical levels. QSAR descriptors were calculated to ascertain the ability of pectin to improve the Oleuropein structure’s hydrophilicity with Log p (-1.171). DFT calculations reveal that the proposed Oleu-Pec structures have stable characteristics and high reactivity with dipole moments up to 7.86 Debye. They also proposed that Pec is most likely to interact with Oleu through physical interaction between its OH group and that of Oleu. MESP maps indicated the active sites revealing their tendency to go through either nucleophilic or electrophilic pathways. Furthermore, global reactivity descriptors were calculated to reveal the improved electronic features of Oleu-Pec structures upon adding Pec to Oleu, proposing it for further promising biomedical applications. The integrated approach of docking and molecular dynamics (MD) simulations applied to the P2Y12 receptor in conjunction with the ligands 2-Oleu(OH)-Pec(OH), Oleuropein, Pectin, compared with native inhibitor (AZJ) provides valuable insights into their binding characteristics. Among these ligands, the 2-Oleu(OH)-Pec(OH) emerges as a highly promising candidate, demonstrating exceptional stability with a docking RMSD of 0.68 Å, a robust binding affinity of -6.80 kcal/mol, and an extensive interaction network comprising 18 total bonds, including 12 hydrogen bonds. MD simulations further validate its stability, showcasing a consistent RMSD (~ 0.41 nm), 2–4 intermolecular hydrogen bonds, and the lowest MM/PBSA ΔG value of -54.64 kcal/mol. Principal Component Analysis (PCA) reinforces these findings by revealing the tightest clustering, indicating minimal conformational variability. The synergy observed between Oleuropein and Pectin in the dual-ligand configuration enhances the overall binding strength, surpassing that of the individual components. These outcomes underscore the potential of 2-Oleu(OH)-Pec(OH) as a promising P2Y12 inhibitor for applications in anti-thrombotic therapy.